Peopled leadership growing people and transforming organizations - Mayers, R. Stewart 1959-; Anderson, Jennifer M. 1971-; Williams, Todd 1963- (Rowman & Littlefield, 2023)
Peopled Leadership is a new dynamic model aimed at creating new leaders and new futures. It is people centric and people oriented with a focus on developing and empowering others, serving with humility, and expressing gratitude. Peopled Leadership provides the much-needed shift from accountability and outcomes focused driven leadership behaviors to behaviors that focus on people, while assuring accountability and organizational improvement. Peopled Leadership is a model which orients a leader’s focus on people and their commitment to the people, organizations, communities, and institutions they serve. This new model empowers others to lead, be innovative, engage in collaboration, solve complex problems, and further outcomes. The result of Peopled Leadership is the transformation of people and the transformation of practices that mitigate the complexities intrinsic to peopled organizations.